SnO2 hollow nanotubes: a novel and efficient support matrix for enzyme immobilization. Issue 1 (December 2017) - Anwar, Muhammad; Kim, Dong; Kumar, Ashok; Patel, Sanjay; Otari, Sachin; Mardina, Primata; Jeong, Jae-Hoon; Sohn, Jung-Hoon; Kim, Jong; Park, Jung; Lee, Jung-Kul
Abstract A major challenge in the industrial use of enzymes is maintaining their stability at elevated temperatures and in harsh organic solvents. In order to address this issue, we investigated the use of nanotubes as a support material for the immobilization and stabilization of enzymes in this work. SnO2 hollow nanotubes with a high surface area were synthesized by electrospinning the SnCl2 precursor and polyvinylpyrrolidone (dissolved in dimethyl formamide and ethanol). The electrospun product was used for the covalent immobilization of enzymes such as lipase, horseradish peroxidase, and glucose oxidase. The use of SnO2 hollow nanotubes as a support was promising for all immobilized enzymes, with lipase having the highest protein loading value of 217 mg/g, immobilization yield of 93%, and immobilization efficiency of 89%. The immobilized enzymes were fully characterized by various analytical methods. The covalently bonded lipase showed a half-life value of 4.5 h at 70 °C and retained ~91% of its original activity even after 10 repetitive cycles of use. Thus, the SnO2 hollow nanotubes with their high surface area are promising as a support material for the immobilization of enzymes, leading to improved thermal stability and a higher residual activity of the immobilized enzyme under harsh solvent conditions, as compared to the free enzyme.